Transformation of Zinc under Aerobic and Anaerobic Conditions in Some Soils of Kandhamal District, Odisha, lndia - , Subhajit Dutta; , Abhiseka Dash; , Suchhanda Mondal (Archives of Current Research International, 2025)
An incubation study was carried out in the laboratories of the Department of Soil Science and Agricultural Chemistry, Visva-Bharati (WB), to study the transformation of native soil zinc fractions under aerobic and anaerobic conditions. Four surface soil samples of different available zinc content (0.408, 0.63, 1.016, 4.194 mg kg-1) were taken for this experiment. Soil samples were collected from farmers’ fields in rice-growing areas of Kandhamal district of Odisha and analyzed for initial physicochemical properties. A five-gram portion of each soil sample was incubated in a 50 mL centrifuge tube at room temperature for a period of 0, 15, 30, 45, 60, 75, and 90 days under both aerobic and anaerobic conditions. Destructive sampling was done, and different zinc fractions were determined after every interval. Both aeration conditions and incubation period largely influenced the transformation of native zinc fractions in soil. Irrespective of the incubation period, the anaerobic condition of the soil resulted in decrease in the content of WSEX-ZN, CRYOX-Zn, OC-Zn, MnOx-Zn, and increased the content of AMOX-Zn and RES-Zn fractions. Under anaerobic conditions, with progress in incubation period, a gradual decrease in WSEX-Zn and CRYOX-Zn fractions and an increase in AMOX-Zn and RES-Zn fractions were observed, whereas the OC-Zn and MnOx-Zn fractions were decreased after showing an increase during the initial period of incubation. Under aerobic conditions, WSEX-Zn, OC-Zn, CRYOX-Zn content decreased, and AMOX-Zn content increased; however, the RES-Zn and MnOx-Zn showed no remarkable changes with the incubation period. The transformation was more remarkable under anaerobic conditions than under aerobic conditions. Thus, anaerobic conditions over the 90-day incubation study helped to decrease the content of WSEX-Zn, OC-Zn, CRYOX-Zn, MnOx-Zn, and to increase the content of AMOX-Zn and RES-Zn. Among the entire zinc fractions studied, both the content and percent contribution of RES-Zn fraction to the total zinc remained highest throughout the incubation study, whereas WSEX-Zn content remained lowest. Change in relative preponderance order of different native zinc fractions was also observed after 90 days of incubation, both under aerobic and anaerobic conditions; however, it was more prominent in the case of the later.